2019
DOI: 10.3390/jcm8030371
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Virtual Reality for Preoperative Planning of Lymphovenous Anastomosis in a Patient with a Complex Lymphatic Malformation

Abstract: The management of lymphatic malformations (LMs) is challenging, particularly for large and complex lesions involving anatomical structures in the adjacent tissue. While lymphovenous anastomosis (LVA) has been reported as an effective treatment for lymphedema, it has hardly been described as a treatment for LM. Virtual reality has the ability to visualize human structures in three dimensions and can be used for the preoperative planning of complex cases. Here, we describe the first case of the management of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 12 publications
(13 reference statements)
0
21
0
1
Order By: Relevance
“…The general benefits of VR that have been identified are now regularly employed in research capacities across the academy. VR and related 3D data-creation tools are being applied to fields such as digital humanities, 11 archaeology, 12 cultural heritage preservation, 13 medieval studies, 14 HTTPS://DOI.ORG/10.6017/ITAL.V38I4.11075 engineering, 15 biology and biodiversity research, 16 medicine, 17 and architecture. 18 In some cases, these approaches draw on the capabilities of 3D/VR to recreate immersive, high-fidelity experiences of real-world spaces, while in other cases, researchers are exploring the capabilities of VR to provide a platform for analyzing spatially oriented research data in the form of 3D models of cultural heritage artifacts and sites or visualizations of multivariate quantitative data.…”
Section: Uses Of Vr In Researchmentioning
confidence: 99%
“…The general benefits of VR that have been identified are now regularly employed in research capacities across the academy. VR and related 3D data-creation tools are being applied to fields such as digital humanities, 11 archaeology, 12 cultural heritage preservation, 13 medieval studies, 14 HTTPS://DOI.ORG/10.6017/ITAL.V38I4.11075 engineering, 15 biology and biodiversity research, 16 medicine, 17 and architecture. 18 In some cases, these approaches draw on the capabilities of 3D/VR to recreate immersive, high-fidelity experiences of real-world spaces, while in other cases, researchers are exploring the capabilities of VR to provide a platform for analyzing spatially oriented research data in the form of 3D models of cultural heritage artifacts and sites or visualizations of multivariate quantitative data.…”
Section: Uses Of Vr In Researchmentioning
confidence: 99%
“…Sharing of these sorts of human models for surgical planning and training through open-source biomedical engineering platforms and collaborative design environments may help to promote the medical impact of these innovative procedures [23] and to progress towards medical device personalization [24]. Exploring connections to virtual surgical planning [25] may open additional continuation lines, especially for patients with malformations, in which virtual planning plays a more relevant role [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recent booming computer techniques also provided new aspects in the utility of ICG. Giacalone et al reported a case with lymphatic malformation treated with preoperative virtual reality planning (24). Brebant et al presented an augmented reality intraoperative ICG lymphography navigated LVA (25).…”
Section: Indocyanine Green (Icg) Lymphographymentioning
confidence: 99%